Terapia ocupacional e a questão social : retratos da formação graduada a partir de um recorte latinoamericano - Bianchi, Pamela Cristina (2016)
The Latin American social issue was built historically by the social relations and concentration of power and wealth of minorities, dominant classes and sectors. Latin America, characterized by economic inequalities and social vulnerabilities, becomes intervention stage of the professionals involved with the social reality and the effectiveness of social policies, as the occupational therapist. The first occupational therapy courses arose in some countries in the region as a technical profession in the 1950s with the support of foreign teachers. Focusing on a scrap from the Latin American context, except the Brazilian reality, this study aimed at understanding how it is carried out the graduate training of occupational therapists to work with contemporary social issues. In 2014 and 2015, period of this study, occupational therapy graduate education was present in 13 countries, in 72 courses, except those allocated in Brazil. To apprehend this scenario, there were employed three moments of data collection and analysis of its results: systematic survey of scientific literature selected in journals of the field and in two occupational therapy congresses held in the region; mapping of the 72 undergraduate courses through the investigation of electronic websites and questionnaires applied with their coordinators, obtaining 40 questionnaires; and conducting 23 interviews remotely with teachers who discuss about social issues in their subjects. The results revealed that the discussions present in the academic formation and scientific literature about the occupational therapeutic activities in socially vulnerable territories, are still scarce and not very representative among the other areas of expertise of the profession, especially those of biomedical nature. Nonetheless, it is observed that has expanded a movement guided in theoretical reflections, more critical and questioning about the use of precepts of individualistic nature towards the social needs of the region. It is considered necessary to develop theoretical and methodological frameworks specific in occupational therapy in Latin American countries, except Brazil, to work with the social question. It is hoped that the study can help to reduce borders between Brazil and the other countries in the region and stimulate new studies in the area regarding the occupational therapy themes and the social issue.